2021
DOI: 10.21037/atm-21-1885
|View full text |Cite
|
Sign up to set email alerts
|

Kv3.1 channelopathy: a novel loss-of-function variant and the mechanistic basis of its clinical phenotypes

Abstract: Background: KCNC1 encodes Kv3.1, a subunit of the Kv3 voltage-gated potassium channels. It is predominantly expressed in inhibitory GABAergic interneurons and cerebellar neurons. Kv3.1 channelopathy has been linked to a variety of human diseases including epilepsy, developmental delay, and ataxia. Characterization of structural and functional disturbances of this channel, and its relationship to a heterogenous group of clinical phenotypes, is a current topic of research. We herein characterize the clinical phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Of note, gating charge mutations R317S and R320H are both loss-of-function variants linked to human channelopathies (Figs. 2d and S5 ) 10 , 11 , 47 . Another notable difference is that a second glutamate, E213 in the S2 segment of Kv3.1a, replaces T184 in the Kv1.2 structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, gating charge mutations R317S and R320H are both loss-of-function variants linked to human channelopathies (Figs. 2d and S5 ) 10 , 11 , 47 . Another notable difference is that a second glutamate, E213 in the S2 segment of Kv3.1a, replaces T184 in the Kv1.2 structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EZR plays a key role in promoting the invasion and metastasis of malignant tumors [48]. KCNC1 encodes a subunit of the Kv3 voltage-gated potassium channels and associated with a variety of human diseases, including ataxia, epilepsy and developmental delay [49]. COLEC12 encodes a member of the C-lectin family, which is a scavenger receptor that plays a crucial role in the binding and clearance of Aβ [50].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that KCNC1 has a wide spectrum of related phenotypes, which can manifest not only as progressive myoclonic epilepsy (PME), but also as non‐PME, infant DEE, and developmental encephalopathy without seizures 36–39 . In China, Li et al 40 found a novel KCNC1 variant in epilepsy patients with symptoms similar to myoclonic epilepsy and ataxia due to potassium channel mutation (MEAK), but with distinct radiological features; the study confirmed it as a loss‐of‐function variant. Liu et al used peripheral blood from epilepsy patients with KCNC1 (c.959G>A) gene mutation to establish induced pluripotent stem cells (iPSCs).…”
Section: Kcnc1 In Epilepsymentioning
confidence: 99%
“…34,35 It has been reported that KCNC1 has a wide spectrum of related phenotypes, which can manifest not only as progressive myoclonic epilepsy (PME), but also as non-PME, infant DEE, and developmental encephalopathy without seizures. [36][37][38][39] In China, Li et al 40 Currently, there is no targeted therapy directed at KCNC1.…”
Section: Kcnc1 In Epilepsymentioning
confidence: 99%